Modelling for insight: Does oil price uncertainty have directional predictability for travel and leisure firms? - Das, Debojyoti; Saurav, Sumit; Dutta, Anupam (Elsevier, 2025)
This study investigates how uncertainty surrounding crude oil prices affects the stock returns of travel and leisure (T&L) companies. Through a comprehensive analysis, we address three key questions: (a) Does oil price uncertainty predict T&L stock returns directionally? (b) How does varying oil uncertainty affect T&L returns under different market conditions? (c) Is this association consistent across continents? Using the implied oil volatility index (OVX) as a proxy for oil price uncertainty and cross-quantilogram modelling, our study reveals significant impacts of OVX on T&L stock returns, with varying predictability across continents. We find that stock returns are more vulnerable mainly during bearish market conditions, with predictability strength varying over time horizons. Our findings highlight the importance for T&L firms to mitigate oil risk exposure, potentially leveraging emerging technologies like electric vehicles. This study provides insights into the interplay between oil uncertainty and T&L stock returns, with implications for industry practitioners, investors, and policymakers aiming to foster sustainable tourism development amidst oil market volatility due to geopolitics.
Keywords: Oil price uncertainty; Travel and leisure; Cross-quantilogram; Tourism; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|